Detection of Antibodies Brucella abortus in dairy cattle in Puspo District, Pasuruan using Rose Bengal Test and Complement Fixation Test - Kusuma, Agung Jati; Safitri, Erma; Praja, Ratih Novita; Tyasningsih, Wiwiek; Yunita, Maya Nurwartanti; Wibawati, Prima Ayu (Jurnal Medik Veteriner, 2021)
Brucellosis was an infectious disease caused by the genus brucella. Brucellosis in dairy cattle was caused by Brucella abortus that impaction an abortion. The aim of this study was to determine the presence of antibodies of the Brucella abortus in adult female dairy cattle in the Puspo district Pasuruan using Rose Bengal Test (RBT) and Complement Fixation Test (CFT). A descriptive analysis method with quantitative approach was used in this study. Meanwhile, interviews were conducted to get supporting information from the farmer. Used 100 samples. The results of the study showed 2% samples considered positive brucellosis tested by RBT. To confidence false-positive result, RBT test was followed by CFT. After tested by CFT, in this study there were no brucella antibodies in adult female dairy cattle in Puspo district, Pasuruan.